ACTR-49. INITIAL EXPERIENCE WITH SCALP PRESERVATION AND RADIATION PLUS CONCURRENT ALTERNATING ELECTRIC TUMOR-TREATING FIELDS (SPARE) FOR GLIOBLASTOMA PATIENTS. (11th November 2019) - Song, Andrew; Ly, Michele; Bar-Ad, Voichita; Werner-Wasik, Maria; Glass, Jon; Martinez, Nina; Andrews, David; Judy, Kevin; Evans, James; Farrell, Christopher; Shi, Wenyin
Abstract: INTRODUCTION: Standard of care for glioblastoma includes concurrent chemoradiation and maintenance temozolomide with electric tumor treatment fields (TTFields). Preclinical studies suggest TTFields and radiation treatment have synergistic effects. We report our initial experience evaluating toxicity and tolerability of scalp-preserving radiation with concurrent TTFields. METHODS: We conducted a single arm pilot study. Adult patients (≥ 18 years old) with KPS ≥ 60 with newly diagnosed glioblastoma were included. All patients received concurrent scalp-preserving radiation (60 Gy in 30 fractions), standard temozolomide (75 mg/m 2 daily), and TTFields (200 kHz; ≥ 18 hr daily). Maintenance therapy included standard temozolomide and TTFields. Radiation treatment was delivered through TTFields arrays. Our primary endpoint was safety and toxicity for concurrent TTFields with chemoradiation in newly diagnosed glioblastoma. RESULTS: Here we report the first seven patients on the trial. Five were male, and 2 female, with median age 58 y/o (range 49–73). Median KPS was 90. Median follow-up was 5.2 months (range 1.4–11.2). MGMT status was unmethylated for 6 patients, and one unknown, and no IDH mutations. Four (57.1%) received gross total resection and three (42.9%) had subtotal resection. All patients completed concurrent chemoradiation plus TTFields without radiation or TTFields treatment interruption or discontinuation. There was no related Grade 3 or higher toxicity. Skin toxicity (erythema, dermatitis, pruritus) was noted in all patients, however, limited to Grade 1 or 2 which resolved spontaneously or responded to topical medications. All patients were alive at time of writing. Two (28.6%) patients had progression, of which one (at 9 months) continued TTFields and temozolomide with bevacizumab, while the other (at 4 months) discontinued TTFields and underwent re-resection with bevacizumab. CONCLUSIONS: Concurrent TTFields with scalp-preserving chemoradiation is a safe and feasible treatment option with limited toxicity. Future randomized prospective trial is warranted to define therapeutic advantages of concurrent TTFields with chemoradiation.